W kregu ziemi i planet - Pokorny, Edward Jerzy; Gadomska, Julitta (Warszawa : Nasza Ksiegarnia, 1967)
An introduction to the study of the planet Earth and its position in the solar system. For highschool students.
Bibliographic references [101]
Keywords: Astronomy -- Observations